Persepsi Masyarakat Terhadap Perempuan di Ranah Politik Lokal Kabupaten Bulukumba - Jusri Adi; Fitriani Sari Handayani Razak; Hendri Kurniawan (Department of Public Administration, Muhammadiyah University of Makassar, 2022)
This study aims to analyze and describe public perceptions of women in the local political sphere of Bulukumba Regency. This study uses a descriptive type of qualitative research. Research informants from Bulukumba Regency KPUD Members, female DPRD members from Bulukumba Regency, community leaders, beginner voters. Data were collected from the results of interviews, observations and documentation, then data analysis through data reduction, data presentation and conclusion drawing. The results of this study indicate that the public perception of women who are involved in local politics in Bulukumba Regency, some people provide support for women to be involved in politics, but on the other hand there are also those who still doubt the ability of women to be involved in the political sphere because of the patriarchal culture that is still inherent in society.